Policies and practices in haemostasis testing among laboratories in Croatia: a survey on behalf of a Working Group for Laboratory Coagulation of the Croatian Society of Medical Biochemistry and Laboratory Medicine - Bronić, Ana (Biochem Med (Zagreb), 2017)
INTRODUCTION: The objective of this survey was to assess current policies and practice in haemostasis testing among both hospital and outpatient laboratories in Republic of Croatia. MATERIALS AND METHODS: A questionnaire with seventy questions divided into nine sections was created in May 2015. Participants were asked about their practice related to test request form, sample collection, prothrombin time (PT) and activated partial thromboplastin time assays, other individual haemostasis assays, point-of-care testing (POCT), reporting of coagulation tests results and quality assurance of procedures, the personnel and other laboratory resources, as well as on issues related to education and implementation of additional coagulation assays in their laboratory. The survey was administered and data were collected between June and September 2015. RESULTS: A total survey response rate was 104/170 (61.2%). Most respondents were faced with incomplete information on prescribed therapy and diagnosis on the test request or inappropriate samples withdrawn on distant locations, but also do not have protocols for handling samples with high haematocrit values. Reporting of PT-INR and D-dimer results was different between laboratories. Although almost all laboratories developed a critical value reporting system, reporting a value to general practitioners is still a problem. Result on coagulation POCT testing showed that not all devices were supervised by laboratories, which is not in compliance with Croatian Chamber of Medical Biochemistry acts. CONCLUSION: Obtained results highlighted areas that need improvement and different practice patterns in particular field of haemostasis testing among laboratories. A harmonization of the overall process of haemostasis testing at national level should be considered and undertaken.